Superconducting nanowire single-photon detector on dielectric optical films for visible and near infrared wavelengths. (6th July 2017) - You, Lixing; Li, Hao; Zhang, Weijun; Yang, Xiaoyan; Zhang, Lu; Chen, Sijing; Zhou, Hui; Wang, Zhen; Xie, Xiaoming
Abstract: The detection efficiency (DE) of superconducting nanowire single-photon detectors (SNSPDs) at 1550 nm has been significantly improved in the past decades as a result of evolution of the optical structure, the materials, and the fabrication process. We discuss the general optical design for a high-efficiency SNSPD based on dielectric optical films that can detect wavelengths from visible to near infrared regions. This structure shows close-to-unity absorption and good insensitivity to the fine wavelength and the incident angle. We demonstrate an SNSPD specifically fabricated for the detection of 1064 nm wavelength with a maximal system DE of 87.4% ± 3.7%. The DEs of the SNSPDs for visible and near infrared wavelengths are also summarized and compared with those of semiconducting detectors.